Upgrade UMKM Melalui Digitalisasi dan Multi-Channel - Antara, Made Ermawan Yoga (LPPM Universitas HKBP Nommensen, 2025)
Abstract Community service is a routine activity carried out by the Student Association (HIMA) of the Management Study Program, Faculty of Economics and Business, National Education University. The main activity of Real Action for Social Activity (REAFOTY) #8 with the theme